DEVELOPING CONSTRUCTIVIST TEACHING AND LEARNING BASED MODULE IN TEACHING ENGLISH AS A FOREIGN LANGUAGE LESSON - Darwis, Nirwana; Nur, Hasriati (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2023)
Teaching English as A Foreign Language based on the constructivist teaching and learning of TBI Study Program at IAIN Bone have its challenge. One of the challenges is providing teaching module. This research is focused on designing Teaching English as A Foreign Language (TEFL) Module based on constructivist teaching and learning. The research applied research and development by using ADDIE model. The subject in this research is students in TBI Study Program. The result of the research shows that the module has practicality and effective to use in Teaching English as A Foreign Language (TEFL) in TBI Study Program IAIN Bone.